2007
DOI: 10.1152/ajpendo.00691.2006
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected evidence for active brown adipose tissue in adult humans

Abstract: The contention that brown adipose tissue is absent in adult man has meant that processes attributed to active brown adipose tissue in experimental animals (mainly rodents), i.e., classical nonshivering thermogenesis, adaptive adrenergic thermogenesis, diet-induced thermogenesis, and antiobesity, should be either absent or attributed to alternative (unknown) mechanisms in man. However, serendipidously, as a consequence of the use of fluorodeoxyglucose positron emission tomography (FDG PET) to trace tumor metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
1,195
2
47

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,572 publications
(1,261 citation statements)
references
References 52 publications
17
1,195
2
47
Order By: Relevance
“…25,[57][58][59] Until recently, the re-appearance of substantial amounts of brown adipocytes in adult humans had been reported only in adipose tissue surrounding pheochromocytomas 54 but recent data obtained from positron emission tomography analysis has led to the unexpected finding of substantial amounts of active brown fat in some anatomical sites of adult humans including the neck region. 60 Thus, regardless of the precise mechanisms eliciting the appearance of 'buffalo humps' in HALS patients, this phenomenon confirms that in adult humans there is a pool of cells in adipose depots capable of proliferation and differentiation into an adipocyte phenotype that includes brown fat-like features.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocytementioning
confidence: 52%
“…25,[57][58][59] Until recently, the re-appearance of substantial amounts of brown adipocytes in adult humans had been reported only in adipose tissue surrounding pheochromocytomas 54 but recent data obtained from positron emission tomography analysis has led to the unexpected finding of substantial amounts of active brown fat in some anatomical sites of adult humans including the neck region. 60 Thus, regardless of the precise mechanisms eliciting the appearance of 'buffalo humps' in HALS patients, this phenomenon confirms that in adult humans there is a pool of cells in adipose depots capable of proliferation and differentiation into an adipocyte phenotype that includes brown fat-like features.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocytementioning
confidence: 52%
“…Both white adipose tissue (WAT) and BAT are characterized by a high lipid storage capacity in intracellular lipid droplets (LDs), but they differ in their physiological functions. While WAT is the primary site for lipid storage, BAT is specialized for non‐shivering thermogenic functions by increasing energy expenditure through uncoupled respiration (Nedergaard et al , 2007). Activation of the BAT has been shown to enhance energy expenditure and glucose tolerance in mice and humans (Peirce et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that beige adipocytes can derive from a distinct precursor and display a gene expression pattern different from that of brown adipocytes 9. Recent studies also reported the presence of BAT and the formation of UCP1‐expressing adipocytes within WAT depots in adult humans 10, 11. In humans, UCP1‐positive adipocytes exhibiting both brown12, 13, 14 and beige13, 14, 15, 16 molecular signatures have been described.…”
Section: Introductionmentioning
confidence: 99%